Advances in Whole-Component Separation and Applications of Biomass - Zerong LIU; Linghao LI; Xiwei XU (能源环境保护)
Biomass represents a fundamental component of the Earth's most abundant renewable resources, distinguished by its renewability and environmental sustainability, thereby serving as a viable alternative to diminishing fossil fuels. Globally, there is an increasing awareness regarding the significance of sustainable energy sources and the necessity for environmental preservation, which has elevated the investigation and utilization of biomass resources to a prominent position. These resources are widely available and come from agricultural residues, livestock manure, and forestry byproducts. The diversity of biomass is complemented by the complexity of its chemical composition, which includes various components such as cellulose, hemicellulose, lignin, and various organic acids. Maximizing the potential of biomass resources for their high-value and diverse applications relies on the implementation of separation technologies that are both efficient and environmentally sustainable. These advanced technologies serve a dual purpose: they are capable of extracting valuable components from biomass while simultaneously reducing the environmental impact. This article explores the complex structural composition of biomass, reviews innovative methods for component separation, and provides insights into the diverse applications of its main components. A particular emphasis will be placed on a thorough analysis of full-component separation technologies, encompassing various methodologies, including organic solvent extraction, the use of deep eutectic solvents, and the application of ionic liquids. Each method will be evaluated in terms of its separation mechanisms, extraction efficiency, and the factors that may influence the process. As the global demand for sustainable, renewable energy sources and environmentally friendly materials continues to grow, there is an urgent need to discover novel separation mechanisms and technologies. These advancements should be based on the prudent use of cost-effective chemical reagents and a commitment to environmentally responsible production practices. By promoting interdisciplinary collaboration, it is feasible to establish a cohesive industrial framework that can address the complexities associated with biomass conversion and utilization. Such collaborative efforts have the potential to significantly enhance the value and versatility of biomass resources, thereby invigorating the biomass energy and materials sector with innovations that are both economically viable and environmentally friendly. In summary, these initiatives are crucial for advancing biomass as a key contributor to global sustainability. They play an essential role in aligning the biomass industry with global sustainable development goals, ensuring that our energy and material requirements are met without jeopardizing the health of our planet.